2012
DOI: 10.1038/cddis.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

A novel angiogenesis inhibitor impairs lovo cell survival via targeting against human VEGFR and its signaling pathway of phosphorylation

Abstract: Colorectal cancer represents the fourth commonest malignancy, and constitutes a major cause of significant morbidity and mortality among other diseases. However, the chemical therapy is still under development. Angiogenesis plays an important role in colon cancer development. We developed HMQ18–22 (a novel analog of taspine) with the aim to target angiogenesis. We found that HMQ18–22 significantly reduced angiogenesis of chicken chorioallantoic membrane (CAM) and mouse colon tissue, and inhibited cell migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…They were stated as Breact with,^Bin same component,^and Bstate change.^And the cutpoint of state change was set as 12 % (Fig. 3) [19]. The study of ITGA2B and ITGA8 gene cluster indicated that in univariate Cox regression model, PIK3CA, SOS1, VWF, PIK3R1, Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…They were stated as Breact with,^Bin same component,^and Bstate change.^And the cutpoint of state change was set as 12 % (Fig. 3) [19]. The study of ITGA2B and ITGA8 gene cluster indicated that in univariate Cox regression model, PIK3CA, SOS1, VWF, PIK3R1, Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Western blot bands demonstrated a decrease in phosphorylation of VEGFR‐2 after treatment with SiO 2 @LDH‐VP16 on A549 cells. There have been studies showing that suppression the phosphorylation of VEGFR‐2 led to inhibition of cancer cell migration and metastasis 47, 48. The prosurvival activity of phosphoinositide 3 kinase (PI3K)/Akt pathway has been identified that actively engages with the migratory process in motile cells, including metastatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphor-protein array, using cell lysates of SKOV3-shCTHRC1 cells and SKOV3-NC cells as control, was performed by a Phospho-Antibody Array kit (CSP100, FullmoonBiosystems, CA) as previously described [27]. Briefly, cell lysates were biotin-labeled by biotin reagent in N, N-Dimethylformamide.…”
Section: Methodsmentioning
confidence: 99%